2020
DOI: 10.1108/rpj-06-2019-0155
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser sintered nano-HA/PDLLA composite microspheres for bone scaffolds applications

Abstract: Purpose The main cause of aseptic inflammation after an in vivo implantation is that Poly(L-lactide) (PLLA) and Poly(D-lactide) have a slower degradation and absorption rate, while Poly(D, L-lactide) (PDLLA) has a much faster degradation rate than PLLA because of its amorphous structure. Also, the hydrolyzate of Hydroxyapatite (HA) is alkaline, which can neutralize local tissue peracid caused by hydrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
(39 reference statements)
1
8
0
1
Order By: Relevance
“…According to the EDS spectra, the elements were mainly C, O, Ca and P. Meanwhile, the Ca/P ratio of the deposits increased from 1.47 to1.65 as the GO-HAP mass fraction increased from 4% to 16%, which were gradually close to the 1.67 of HAP [10] . The results revealed that the PLLA/GO-HAP scaffolds owned well bioactivity to induce bone-like apatite layer, which was vital to form a chemical bond between the implant scaffold and living bone tissue [13] , [45] . Previous studies had demonstrated that pure PLLA lacked bioactivity, therefore the well bioactivity was attributed to GO-HAP [11] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the EDS spectra, the elements were mainly C, O, Ca and P. Meanwhile, the Ca/P ratio of the deposits increased from 1.47 to1.65 as the GO-HAP mass fraction increased from 4% to 16%, which were gradually close to the 1.67 of HAP [10] . The results revealed that the PLLA/GO-HAP scaffolds owned well bioactivity to induce bone-like apatite layer, which was vital to form a chemical bond between the implant scaffold and living bone tissue [13] , [45] . Previous studies had demonstrated that pure PLLA lacked bioactivity, therefore the well bioactivity was attributed to GO-HAP [11] .…”
Section: Resultsmentioning
confidence: 99%
“…The water contact angle of the PLLA/GO-HAP scaffolds with 4%, 8%, 12% and 16% mass fractions of GO-HAP were 74.1°, 65.9°, 58.7° and 53.6°, respectively. The decrease was ascribed to the incorporation of GO and HAP with good hydrophilicity [13] . Therefore, the scaffold presented an increase in hydrophilicity with the increasing content of GO-HAP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, native bone tissue has a complex structure both in terms of architecture and composition [ 156 ]. Still, additive technologies allow controlling scaffold’s 3D structure [ 157 , 158 , 159 ], while the usage of hybrid polymer/inorganic microparticles containing calcium phosphates mimic natural bone composition [ 160 , 161 , 162 ]. PCL powder was transformed into a porous scaffold with the aim of selective laser sintering technology, coated by collagen and used for chondrocytes culture [ 163 ].…”
Section: Biomedical Applications Of Mpsmentioning
confidence: 99%
“…Many CaPs, such as hydroxyapatite (HA), β-tricalcium phosphate (β-TCP), α-TCP, biphasic HA/β-TCP, tetracalcium phosphate and octacalcium phosphate, have been used to produce scaffolds by SLS, SLA, P-3DP and DIW [ 15 , 16 ]. In the SLS process, the ceramic powders are usually blended with polymers such as PLA [ 17 ], PDLLA [ 18 ], PCL and PEEK [ 19 ] to form composite materials, in order to avoid the high operating temperatures that are required for sintering [ 10 ]. In P-3DP, SLA and DIW, instead, powders are used alone or in suspensions or pastes, with this allowing for the fabrication of pure CaPs scaffolds.…”
Section: Introductionmentioning
confidence: 99%